Relevansi Diskursus Kesetaraan Jender Pada Pemikir Muslim Indonesia di Era Post-Reformasi - Jauhar Azizy; Muhammad Sairi (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2019)
This article will decipher a re-reading of the Qur’anic verses on gender equality that arestill understood by gender bias, especially women bias. The authors see that there are still many behaviors and thoughts that lead to gender bias, especially women bias. The re-readings of Islamic doctrines, especially those of the Qur’an and ḥadīth, are important as a counterweight to gender biased understandings, especially those those found in classical religious texts. The conclusions of this article emphasize that Islam recognizes gender equality between men and women, especially in termsof role and public domain. Men and women have the same opportunity and potential as God’s representatives (khalifatullāh) of the earth who govern and manage the earth’s resources. Only spiritual aspects (piety) distinguish them as human beings in the presence of Allah swt.